Gambaran Caffeine Addiction Pada Ibu Rumah Tangga - Restu Ayu Eka Pustika Dewi; Sri Maryanti; Nunung Nur Aini (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Caffeine is still a popular processed food or drink among teenagers and adults, as well as housewives who still have the habit of consuming caffeine such as coffee or tea. Caffeine as an antagonist at the adenosine receptor will stimulate dopaminergic activity which will cause psychostimulant properties, namely providing a wakeful and arousing effect which can then lead to potential addiction or addiction to caffeine. Consuming caffeine in excess of the daily limit can cause side effects including anxiety, insomnia, increased heart rate, and gastrointestinal disturbances. Therefore, the purpose of this study was to determine the description of caffeine addiction in housewives. The research method using descriptive analysis with sampling using cross sectional technique obtained a sample of 33 people. The data was obtained from filling out questionnaires by respondents about caffeine addiction, then the questionnaire was tested for validity and reliability. The results obtained from the validity test of 9 questionnaire questions, namely r count > r table (0.344), it can be concluded that the questionnaire is valid. Furthermore, the reliability test on the questionnaire obtained the results of the Cronbach alpha value of 0.933 which means > 0.6 so it can be concluded that the questionnaire in this study is said to be reliable. To find out the description of caffeine addiction in respondents, univariate analysis with SPSS showed that most respondents experienced caffeine addiction in the moderate category, namely 29 respondents (87.9%), and 4 respondents (12.1%) experienced caffeine addiction in mild category. The conclusion of this study is that housewives experience caffeine addiction in the moderate category, namely 29 respondents. The importance of limiting daily caffeine intake to minimize the risk of addiction to caffeine and the side effects caused by caffeine.